Evaluating community adoption and participation in water and sanitation interventions in the Bongo District, Ghana - Atengdem, Ruth Amaabadek; Abobi, Seth Mensah; Alhassan, Elliot Haruna (Frontiers in Water, 2024)
Access to improved water and sanitation is a major conduit to meeting global development goals. This has resulted in the proliferation of various improved water and sanitation interventions in most communities of the world. Little evidence, however, exists in Ghana to reveal the extent to which these interventions are being adopted and sustained by the communities they are intended to benefit. This study, therefore, sought to assess the adoption of water and sanitation interventions and their sustainability. The mixed method approach, guided by the concurrent mixed method design was implemented in the Bongo District. Quantitative data were obtained from 389 sampled households in the District with the aid of a survey. Thereafter, univariate and bivariate statistics were used to analyze the quantitative data with the aid of STATA version 15. The qualitative data on the other hand was collected from officials of the District Water and Sanitation Management Team (DWSMT) and members of the water and sanitation management committees at the community level through key informant interviews and focus group discussions. The qualitative data was analyzed manually using thematic analysis. The study found a high adoption rate of both water and sanitation interventions in the Bongo District. The household demographic characteristics that were found to have a strong positive association with the adoption of improved water or sanitation interventions included the sex of household head, age, level of education and household size among others. Major factors influencing the adoption of water and sanitation interventions found included the knowledge of the derived benefits of the facilities and education on the use of the facilities. The study also found that as part of activities geared towards sustainability, most community members were involved in deciding the appropriateness of these water and sanitation facilities; siting of the facilities; and cash contributions. The study, therefore, concludes that the extent of adoption of water and sanitation in the Bongo District is relatively high and communities were involved to some extent to engender the sustainability of the facilities.